Dental Amalgam and Multiple Sclerosis: A Systematic Review and Meta-Analysis - Kevin K. Aminzadeh, Bsc Pharm, DDS; Mahyar Etminan, PharmD, MSc (Blackwell Synergy, 2007)
Amalgam restorations have long been controversial due to their mercury content. Allegations that the mercury may be linked to nervous disorders such as Alzheimer’s, chronic fatigue syndrome, and multiple sclerosis (MS) have fueled the calls for the removal of amalgam restorations from dentists’ armamentarium.